Incomplete construction as a contaminant of the urban environment. Case study of the city of M’sila, Algeria - Feloussia, Lahcene (Technium Social Sciences Journal, 2022)
Most of them are incomplete in terms of construction. The phenomenon is considered to be a topic of study and analysis because it has given an inappropriate picture of the public view, distorted the city’s aesthetic image and become a contaminated phenomenon in the field of visual pollution. The importance of this study lies in trying to understand the real causes of this urban phenomenon and identify the social dimensions and elements of it, economic and cultural that have contributed to its aggravation at the national level. The topic also dealt with the study and analysis of Law 08/15 aimed at finding effective solutions to the phenomenon of incomplete construction and settling the status of buildings of several levels, the most important of which is real estate settlement, conformity and issuance of building permits and others. The field study that touched the city of M’sila through the neighborhood of 295 dwellings (Lamayar neighborhood), which served as a model for this study, also found the reasons for the exacerbation of this phenomenon. At the level of real estate status, at the level of physical and economic capabilities. The population, as well as the level of urban culture.